An Analysis of Competitiveness and Determinants of Indonesia Coal’s Export to Main Destination Country in the 2012-2022 Period - Rendi Renaldi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the competitiveness and factors affecting Indonesia's coal export value. The study uses a quantitative research approach and secondary data types. The analytical technique used to determine competitiveness is the Revealed Comparative Advantage (RCA) index, and to identify the factors influencing Indonesia's coal export value, panel data regression with the Gravity Model is used. The results show that Indonesia's coal commodities have competitiveness in the global market, and the factors such as the Gross Domestic Product (GDP), exchange rate, and carbon dioxide emissions have a significant positive impact, while economic distance has a negative impact on Indonesia's coal export value. The implications of the findings in this study suggest that Indonesia needs to consider the challenges and threats to coal demand from destination countries and diversify products beyond coal to maintain foreign exchange revenue.